Ipsa: Hispaniae fluvius. Boccaccio y el Papiro de Artemidoro (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In the context of the polemic developed since 2006 on the authenticity of the Artemidorus Papyrus, this paper offers a critical review of the arguments on the explanation of the pre-Roman place names of Ipsa and Kilibe proposed by the scholars who defend the fake character of the document. The study highlights the discordance between some of the proposed explanations, and the lack of support of others, concluding that the opinion in favour of the authenticity of the papyrus is still the most plausible one.
Keywords: Artemidorus Papyrus; Authenticity; Polémica; Ipsa; Kilibe